2016
DOI: 10.1080/09712119.2016.1220384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal changes on physiological variables, haematology and serum thyroid hormones profile in male Red Sokoto and Sahel goats

Abstract: The aim of this study was to evaluate the physiological responses of adult male Red Sokoto goats (n = 10; indigenous to the Guinea Savannah climate) and Sahel goats (n = 10; indigenous to the Sahel climate) at the peak of the cold-dry (CDS), hot-dry (HDS) and rainy seasons prevailing in the Guinea Savannah zone of Nigeria. Results revealed that Red Sokoto goats had significantly higher rectal temperature (RT), PCV, red blood cell (RBC), Hb, thyroxin (T 4 ), but lower respiratory rate (RR) and total leucocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
(47 reference statements)
2
26
1
Order By: Relevance
“…Severe dehydration has been reported in livestock exposed to thermal stress, which ultimately led to an increase in PCV, RBC and Hb (McManus et al, 2009;Sejian et al, 2014;Habibu et al, 2017). Thus, heat stress during the HDS was likely responsible for the high PCV and RBC observed in the current study, apparently due to increased thermoregulatory loss of body fluids.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…Severe dehydration has been reported in livestock exposed to thermal stress, which ultimately led to an increase in PCV, RBC and Hb (McManus et al, 2009;Sejian et al, 2014;Habibu et al, 2017). Thus, heat stress during the HDS was likely responsible for the high PCV and RBC observed in the current study, apparently due to increased thermoregulatory loss of body fluids.…”
Section: Discussionmentioning
confidence: 43%
“…1; Nicholson, 1995). Although a previous study reported higher erythrocyte membrane integrity in Sahel than Red Sokoto kids during the HDS (Habibu et al, 2016a), the higher relative humidity in the Guinea savanna of Nigeria may be a negative factor influencing thermoregulation of Sahel kids in the geographical area and may be responsible for the changes observed in erythrocytic parameters observed during the HDS (Habibu et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations